The effectiveness of the Malaysian public sector service delivery system: an analysis / Roshidi Hassan - Hassan, Roshidi (Universiti Teknologi MARA, Shah Alam, 2010)
The Malaysian public sector has contributed a lot in transforming the country's low-value added agriculture-based economy 50 years ago into what it is today as acknowledged by many. A shining example of a success story in economic transformation, Malaysia is a country that has sought and achieved economic development while maintaining its traditional culture and values, and it has judiciously adapted the civil service to support its national objectives. In the transformation process, numerous performance enhancement initiatives were undertaken by the public sector in its effort to adapt to the changing internal and external environment. Despite such efforts undertaken, grouses and complaints from unsatisfied stakeholders and customers are often heard. This paper highlights the concepts of customer satisfaction, the role of organizational stakeholders and organizational performance. It also examines from an internal systems approach why performance enhancement initiatives introduced in public sector organizations in Malaysia fall short of producing the desired results as perceived and expected by the stakeholders. Recommended strategies and action plan to remedy the situation are also included for considerations by interested parties.